TLR Agonists as Modulators of the Innate Immune Response and Their Potential as Agents Against Infectious Disease - Mifsud, Edin J.; Tan, Amabel C.; Jackson, David C. (Frontiers in Immunology, 2014)
Immunotherapies that can either activate or suppress innate immune responses are being investigated as treatments against infectious diseases and the pathology they can cause. The objective of these therapies is to elicit protective immune responses thereby limiting the harm inflicted by the pathogen. The Toll-like receptor signaling pathway play critical roles in numerous host immune defenses and have been identified as a immunotherapeutic target against the consequences of infectious challenge. This review focuses on some of the recent advances being made in the development of TLR ligands as potential prophylactic and/or therapeutic agents.